Increased concentration of sialidases by HeLa cells might influence the cytotoxic ability of NK cells - Wen-Chi Lee; Wen-Ling Lee; Wen-Yuann Shyong; Ling-Wei Yang; Min-Chun Ko; Bor-Ching Sheu; Shie-Liang Edmond Hsieh; Peng-Hui Wang (Elsevier, 2012)
Objective: Cancer cells reportedly have the ability to escape from the immune system, mainly from natural killer (NK) cells. Although the real mechanisms are complicated, some inhibitors that are secreted from the cancer cells might play an important role. This study's aim was to investigate the potential mediator released by cancer cells (HeLa) that contributes to the decreased cytotoxicity of NK cells. Methods and Materials: An NK-HeLa coculture system was used to test the hypothesis that the presence of the potential mediator from cancer cells contributes to the decreased cytotoxicity of NK cells. Results: After coculturing with HeLa cancer cells, the cytotoxicity of NK cells was decreased. When the coculture medium and culture medium containing commercialized sialidase were used to culture NK cells, the cytotoxicity of the NK cells was also inhibited. However, cytotoxicity was partially restored by a sialidase inhibitor (DANA). Western blot analysis of the HeLa cells after coculturing with NK cells demonstrated increased Neu2 and Neu3 expression in HeLa cells. Conclusions: The finding that Neu2 and Neu3 expression in cancer cells might be involved in the impaired function of NK cells, which could be restored by a sialidase inhibitor, provides a new concept that could be applied to the management of cancer.